#### Answer

Even

#### Work Step by Step

$f(-x)=1+3(-x)^{2}-(-x)^{4}=1+3x^{2}-x^{4}=f(x)$
$\therefore f(x)$ is even.

Published by
Cengage Learning

ISBN 10:
1285741552

ISBN 13:
978-1-28574-155-0

Even

$f(-x)=1+3(-x)^{2}-(-x)^{4}=1+3x^{2}-x^{4}=f(x)$
$\therefore f(x)$ is even.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.